Analysis Of Biogas Pressure Based On Mass Variation Of Raw Material Using 150 L / Tank Digester Capacity - Ahmad yunus nasution; Gunawan Hidayat; Abdurra’uf Ibnu Sabio (Fakultas Teknik UM Pontianak, 2020)
Biogas pressure produced in a period of 10 days is 0.001 kg on the 3rd day to 0.013 kg on the 10th day or equivalent to an average of 0.0013 kg / day, which in each day experiences a different increase. The raw materials used are 8 kg cow dung and 2 kg pineapple skin waste with a raw material ratio of 4: 1 and 10 liters of water are added mixed with EM4. In this study, the authors compared the biogas pressure produced from a mixture of raw materials from cow manure and pineapple peel waste with biogas produced from a mixture of raw materials from cow dung and water hyacinth. The research method used is literature review, interviews and then the data collected will be used to calculate the ratio of biogas pressure. From the results of the biogas pressure comparison it was found that the mixture of raw materials for cow dung and water hyacinth was more effective than biogas with raw materials for cow dung and pineapple skin waste with a fermentation process within 10 days.